Pengaruh Kompensasi dan Deskripsi Pekerjaan terhadap Etos kerja karyawan PT. BMAJ - Budianto, Budianto (JOURNAL ECONOMICS AND STRATEGY, 2025)
This research uses quantitative descriptive research. The total population in the study was 126 employees with the sampling technique using the Slovin formula 95% confidence level and 5% error tolerance so that from the calculations obtained as many as 96 samples. Simultaneously there is a significant effect between compensation and job description variables on the work ethic of employees of PT. BMAJ. While partially found compensation variables have a significant effect on the work ethic of employees of PT. BMAJ. Partially it was found that the job description variable had a significant effect on the work ethic of the employees of PT. BMAJ.